IMPLEMENTASI PENILAIAN AUTENTIK BERBASIS HOTS DI KELAS VD SD NEGERI 13/1 RENGAS CONDONG MUARA BULIAN - Agung Rimba Kurniawan; Faizal Chan; Muhammad Agus Mubarok; Eka Purwanti; Islami Citra; Anggi Kurnia; Ahlina Mursalati Urfa (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study was designed to describe the authentic implementation of HOTS based on SD Negeri 13/1 Rengas Condong, Muara Bulian. This study uses qualitative types of phenomenology. Phenomenology is a type of research that discusses, describes, explains related to the phenomena that occur. The sampling technique was purposive sampling and the informants in this study were VD class teacher SDN 13 / I Rengas Condong. Data collection is taken by observation, interview, and collection techniques. Data analysis techniques were performed using qualitative models from Miles and Hubberman (reduction, display, data verification). The results showed that the classroom teacher had implemented authentic. While the authentic resent that the teacher has done are: 1). Attitude assessment is only done by observation techniques, while peer assessment and self-assessment techniques are not carried out on the grounds that the teacher manages the class and difficulties with the assessment criteria based on the rubric on the attitude assessment instruments in the book; 2). Further Attention. The questions given by the teacher to students are not in accordance with HOTS, this is because the teacher is only fixated on existing books and does not develop questions based on HOTS; 3). Related to the expertise and projects that have been carried out in practicum activities and student group work. Based on these results, it is undeniable that the HOTS-based authentic practice conducted by the VD grade teacher SDN 13/1 Rengas Condong, Muara Bulian has been going quite well. Suggestions that can be given, while asking teachers who follow the guidelines Get authentic according to the revised 2013 curriculum, and the teacher who asks can develop questions based on HOTS.